Exploring cognitive discourse functions for disciplinary literacies in university EMI programs - Kurt, Yavuz; Gülle, Talip; Bektaş Yüksel, Sezen; Bayyurt, Yasemin (Glottodidactica, 2025)
This study investigates the integration of Cognitive Discourse Functions (CDFs) in English-Medium Instruction (EMI) classrooms across various disciplines in Turkish higher education, with a particular focus on teacher education programs. CDFs provide a systematic framework for analysing how language facilitates cognitive processes such as describing, explaining, evaluating, and categorising in disciplinary contexts. The data comprise 472 minutes of lesson recordings from five courses across three fields: Computer Education and Educational Technology, English Language Teaching, and Mathematics and Science Education. Lessons were analysed using CDF coding to examine field-specific variations in language use and their implications for disciplinary literacies. The study provides an initial exploration of the interconnectedness of CDFs with disciplinary literacies by delineating their role in building foundational knowledge, facilitating reasoning, and fostering critical thinking. These findings indicate that explicit integration of CDFs into EMI pedagogy has potential for addressing language and content challenges faced by students in EMI settings. The article contributes to the growing body of research on EMI by providing insights into the interplay between language and disciplinary knowledge construction.